Contours of death and disease in early modern England - Dobson, Mary J. (New York, NY, USA : Cambridge University Press, 1997)
Using a wide range of sources for the south-east of England, Dobson highlights the tremendous variation in levels of mortality across geographical contours and across two centuries, exploring the causes and consequences of these variations.
1. Airs, waters and places -- 2. Regional and local settings -- 3. Geographical patterns of mortality -- 4. Geographical rhythms of mortality -- 5. The spectrum of death, disease and medical care -- 6. Marshlands, mosquitoes and malaria -- 7. Crises, fevers and poxes -- 8. The epidemiological landscapes of the past.
Includes bibliographical references (pages 540-621) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Sussex; Diseases -- England, South East -- History -- 17th century; Diseases -- England, South East -- History -- 18th century; Mortality -- England, South East -- History -- 17th century; Mortality -- England, South East -- History -- 18th century; Diseases -- England, South East -- Statistics; Mortality -- England, South East -- Statistics; Medical geography -- England, South East; Medicine -- History -- 17th century; Medicine -- History -- 18th century; Mortality; Diseases -- England, South East -- Statistics; Mortality -- England, South East -- Statistics; Disease Outbreaks -- history; History, 17th Century; History, 18th Century; Mortality; England; Maladies -- Angleterre (Sud-Est) -- Histoire -- 17e siècle.; Maladies -- Angleterre (Sud-Est) -- Histoire -- 18e siècle.; Mortalité -- Angleterre (Sud-Est) -- Histoire -- 17e siècle.; Mortalité -- Angleterre (Sud-Est) -- Histoire -- 18e siècle.; Maladies -- Angleterre (Sud-Est) -- Statistiques; Mortalité -- Angleterre (Sud-Est) -- Statistiques; Géographie médicale -- Angleterre (Sud-Est); Maladies -- Angleterre (Sud-Est) -- Statistiques; Médecine -- Histoire -- 17e siècle.; Médecine -- Histoire -- 18e siècle.; Mortalité.; mortality; MEDICAL -- Health Risk Assessment; MEDICAL -- Epidemiology; Medicine; Diseases; Medical geography; Mortality; England -- England, South East; Bevölkerung; Krankheit; Todesursache; Sterblichkeit; Kent; Essex; England -- Südost; Ziekten; Sterfte; Épidémiologie -- Grande-Bretagne (sud-est) -- 1500-1800.; Mortalité -- Grande-Bretagne (sud-est) -- 1500-1800.; Maladies -- Grande-Bretagne (sud-est) -- 1500-1800.; Santé et hygiène -- Grande-Bretagne (sud-est) -- Histoire; Geschichte (1600-1800); Geschichte 1600-1800.; 1600-1799; History; Statistics